2019
DOI: 10.1021/acssuschemeng.8b05549
|View full text |Cite
|
Sign up to set email alerts
|

Photon-Free Degradation of Dyes by Ge/GeO2 Porous Microstructures

Abstract: Several industries use dyes as coloring agents and release untreated effluents in the form of wastewater that has created panic due to the environmental issue. Considerable efforts have been extended to develop photocatalysts for the degradation of these dyes. Here, we report the photon-free degradation of various cationic and anionic dyes for the first time by Ge/GeO 2 porous microstructures. The degradation efficiency and time are found to be dependent on the catalyst amount, and it is possible to achieve ∼1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The trapping and release of photogenerated electrons enable many photocatalysts to be active even after the light was turn off. We expect a similar effect in the case of TSCT. The experimental observation clearly demonstrates that the degradation capability of TSCT sample in the dark was due to its large number of trapped paramagnetic species (confirmed by EPR measurement), which provided its memory of the light illumination prior to the dark environment.…”
Section: Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The trapping and release of photogenerated electrons enable many photocatalysts to be active even after the light was turn off. We expect a similar effect in the case of TSCT. The experimental observation clearly demonstrates that the degradation capability of TSCT sample in the dark was due to its large number of trapped paramagnetic species (confirmed by EPR measurement), which provided its memory of the light illumination prior to the dark environment.…”
Section: Results and Discussionmentioning
confidence: 83%
“…A new peak appears near 350 nm, due to the semi-reduced methylene blue radical 46,49 . Figure 9c The trapping and release of photogenerated electrons enable many photocatalyst to be active even after the light was turn off [50][51][52][53][54] . We expect similar effect in case of TSCT.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that there were also the degraded products in the unfaded parts. Shinde et al reported that cationic MG could also be degraded with photon-free catalysts by donating electrons from the metal core or by creating hydroxyl radicals [ 31 ]. Now that this is unavoidable, the faded textiles should strictly be kept away from light in a certain humidity of 50–65% RH, according to a preventive conservation principle from the International Institute for the Conservation of Historic and Artistic Works (IIC) that humidity levels over 65% may cause mold, corrosion, and shrinkage, and that dryness levels under 50% may cause breakage and desiccation.…”
Section: Resultsmentioning
confidence: 99%
“…In the artificial accelerated photoageing experiment, malachite green degraded in methanol under the action of the high reactivity of superoxide species or free radicals. There were many ways to introduce the trace metal ions as photocatalysts that generated reactive oxygen species (ROS) [31], such as the solvent impurities introduced by industrial synthesis [32] and the equipment used or exposed during the aging experiments, which inevitably promoted the catalytic reaction, though a longer aging time was required. Similarly, it was impossible to avoid contact with the metal utensils during the entire dyeing process.…”
Section: Discussion Of the Fading Mechanism Of Mg Industrial Dye In T...mentioning
confidence: 99%
“…Another method for sewage treatment is to decompose toxic substances into harmless compounds directly . Semiconductor photocatalysts are widely used to decompose dyes, and many semiconductor materials, such as titanium dioxide (TiO 2 ), zinc sulfide (ZnS), and zinc oxide (ZnO), have been reported to degrade complex chemicals, especially dyes. , Possessing ideal properties such as nontoxicity and low cost and displaying a photocatalytic activity under the irradiation of ultraviolet light (UV light), TiO 2 nanoparticles (TiO 2 NPs) also have the ability to decompose dyes into soluble nontoxic ions and small molecules . Thanks to the large specific surface area, TiO 2 NPs have been studied in the field of water treatment. , However, the separation of TiO 2 NPs from the water is too cumbersome, limiting the application of TiO 2 NPs in commercial or industrial water treatment .…”
Section: Introductionmentioning
confidence: 99%